Kampung Cumi: Semarak Festival dan Pengembangan Ekonomi Desa Langgula - Nanda W. Kountu; Helman Manay; Irvan Tasnur (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the role of the Kampung Cumi Festival in the economic development of the Langgula Village community through a local socio-cultural perspective. The background of this study stems from the need for a coastal village development model capable of sustainably integrating the economic potential of fisheries with the community’s cultural practices. The research approach employs an empirical qualitative descriptive design, utilizing data collection techniques such as field observations, in-depth interviews, and documentary studies of the social actors involved in the festival. The findings indicate that the Kampung Cumi Festival serves as a space for creative economic empowerment centered on processed squid products, while also functioning as a medium for reproducing local cultural values such as mutual cooperation and the transmission of traditions. Community participation strengthens the village’s social capital and enhances the capacity of SMEs in product innovation and collective promotion. The festival also fosters the integration of culture, economy, and village institutions, thereby creating an adaptive and inclusive development ecosystem. The novelty of this research lies in the analysis of cultural festivals as instruments for sustainable village economic development rooted in the social identity of coastal communities.